Yellowknife Old Town -- photograph - Seale, Linda N. (1965)
Yellowknife Old Town, looking east from Akaitcho Hall. Franklin Avenue centre, Back Bay to the left, Latham Island centre distance, Yellowknife Bay to the right. September 1965